Approximations and endomorphism algebras of modules - Göbel, R. (Rüdiger), 1940-; Trlifaj, Jan (De Gruyter expositions in mathematics, 2012)
This monograph -- now in its second revised and extended edition -- provides a thorough treatment of module theory, a subfield of algebra. The authors develop an approximation theory as well as realization theorems and present some of its recent applications, notably to infinite-dimensional combinatorics and model theory. The book starts from basic facts and gradually develops the theory towards its present frontiers.